The Influence of the Managerial Competence of the Principal on Teacher Performance at MAS Al-Washliyah 22 Tembung - Filma Muhazri Sembiring; Candra Wijaya (Didaktika: Jurnal Kependidikan, 2024)
This study aims to examine the Influence of Madrasah Principal Managerial Competence on Teacher Performance at MAS AL-Washliyah 22 Tembung using a quantitative method. The research design employed is correlational. There are two variables in this study, the independent variable being Principal Managerial Competence (X), and the dependent variable being Teacher Performance (Y). The results of the study indicate that in the partial t-test, the significance value (sig.) is 0.000 < 0.05. Therefore, it can be interpreted that there is a significant influence of madrasah principal managerial competence on teacher performance at MAS Al-Washliyah 22 Tembung. Furthermore, based on the statistical model Summary, the R Square value is 0.606 or 60.6%. Thus, it can be interpreted that the magnitude of the influence of madrasah principal managerial competence on teacher performance at MAS Al-Washliyah 22 Tembung is 60.6%. The magnitude of this influence is categorized as strong.